The Nexus: Energy, Environment and Climate Change (Green Energy and Technology,, 2018)
This book focuses on the water-energy-climate nexus, which can be used to improve energy security and quality of life for millions of people in developing countries. It enhances the reader's understanding of the link between energy and climate, through the development of new approaches to and methods for energy generation, energy use, and climate change adaptation and resilience. By presenting case studies and research reports, the book addresses the relevant issues needed in order to analyze and successfully implement technologies in the water-energy-climate nexus. It focuses on the contributions of higher education institutions in terms of capacity-building for energy efficiency, energy access and energy security, as they relate to climate change mitigation. The book combines results from the authors' own research with detailed analyses, and the research presented lays the foundation for innovative new concepts and ideas, which the authors subsequently discuss. The book will appeal to all those interested in the links between energy issues, sustainability and climate change, as it focuses on the exchange between science and technology experts, as well as decision makers. It also supports students studying renewable energies and energy security, while serving as a valuable reference source for researchers, professionals, practitioners and scientists.